Fetomaternal outcome in women with heart disease in urban population in a tertiary care hospital - Sharma, Preeti; Malik, Renuka (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2018)
Background: Heart disease in pregnancy is still a major problem worldwide, particularly in low resource country like India. Its reported incidence varies between 0.1 to 4%. Heart disease complicates 1% to 3% of all pregnancies and is responsible for 10% to 15% of maternal mortality. In India, the rheumatic heart disease (RHD) contributes to approximately 70% of heart disease seen in pregnancy. Heart disease in pregnancy is associated with adverse fetomaternal outcome and has re-emerged as one of the leading causes of maternal mortality. The maternal mortality rate in women with cardiac disease is 7% and morbidity is 30% during pregnancy in India. Methods: This study was a prospective observational study conducted in the department of obstetrics and gynaecology at PGIMER & Dr. RML hospital from Nov 2015 to March 2017. 35 Pregnant women with heart disease were taken as study group and 35 low risk pregnant patients were taken as control. Multiple pregnancy and any other medical disorder like GDM, PIH, IHCP and thyroid disorders were excluded from study. Fetomaternal outcome in terms of POG at delivery, mode of delivery, prematurity, LBW, NICU admission and maternal and neonatal mortality were compared between these two groups. Results: Vaginal delivery is still the common mode of delivery. Preterm delivery, prematurity, ICU admission, low birth weight is more common in pregnancy with heart disease than in normal pregnancy. Conclusions: Although maternal mortality and fetal mortality is reduced, pregnancy with heart disease still carries substantial risk to mother and child.